Smart Parking System using Android and QR Code for Widyatama University - Faza, Yuqbal Faza Aula Dipa (IJCONSIST JOURNALS, 2020)
With so many vehicle users, a new problem arises, namely the unorganized parking lot with the lack of a proper parking management system. These create various problems for vehicle users who want to park their vehicles, such as losing much time to find an empty parking space, besides that a manual parking payment system can result in long queues at payment counters and this happened at Widyatama University because it needs the right solution to overcome these problems. With the concept of a smart parking system that uses the QR Code for user convenience. This system can run on cellular platforms with a visual display that makes it easy for users. Besides, users can reserve a parking space before parking their vehicle. With additional features of the automatic payment system (E-money). This system can streamline time and efficiency. The research method was carried out using a prototype method in the method of making the system a structured process and has several stages that must be passed. Therefore this method aims to design cellular applications, "Parkirin Aja!".